Chitosan as an ocular drug delivery vehicle for vancomycin - Khangtragool A. (2014)
The main objective of this research has been to study the efficiency of chitosan as an ocular drug delivery vehicle for topically applied vancomycin in rabbit eyes. Vancomycin 50 mg/mL was reconstituted in four preparations, namely: in Tears Naturale II™, in 0.9% w/v aqueous sodium chloride, and in 0.1% and 0.3% w/v chitosan solutions in 1% aqueous L(+)-lactic acid. Twenty-five microliters of vancomycin (50 mg/mL) were applied into the lower conjunctival eye sac in rabbit eyes. Tear samples were then collected after 0, 30, 60, 90, and 120 min to evaluate the pharmacokinetics of the topically applied vancomycin. Comparison of the results obtained showed that vancomycin 50 mg/mL eye drops in the 0.3% chitosan solution were similar to Tears Naturale II™ in terms of bioavailability. The main conclusion to be drawn from this study is that the 0.3% w/v chitosan solution appears to be a highly promising, cost effective candidate for biomedical use as a vehicle for vancomycin ocular drug delivery. Copyright © 2010 Wiley Periodicals, Inc.